2018
DOI: 10.1080/19475705.2018.1470112
|View full text |Cite
|
Sign up to set email alerts
|

Geoinformatics vulnerability predictions of coastal ecosystems to sea-level rise in southeastern Australia

Abstract: Coastlines are dynamic environments, with their Eco-geomorphology controlled by a complex range of natural and anthropic processes. Estuarine environments and associated wetland ecosystems are a critical shoreline types with regards to biodiversity, and are particularly susceptible to the influence of sea-level rise. This project applied future sea-level rise of Intergovernmental Panel on Climate Change (IPCC) hydro-scenarios to assess its impact on the ecogeomorphic aspects of coastal ecosystems in terms of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This result showed that the island is dynamic after the tsunami and around 464 ha of beach area got lost during the period of . During 2005to 2018, the majority of the coastal areas showed accretion around 42.6% and erosion in the range of 24.6% (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…This result showed that the island is dynamic after the tsunami and around 464 ha of beach area got lost during the period of . During 2005to 2018, the majority of the coastal areas showed accretion around 42.6% and erosion in the range of 24.6% (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC) scenarios predict that for RCP8.5 rates could be as high as approximately 12 mm/yr, whilst RCP 6.0 and RCP4.5 show rates of change between 6 and 8 mm/yr and RCP 2.6 significantly lower at 4 mm/yr (Pörtner et al, 2019). Overall, predicted SLR appears to be similar to global mean sea-level (GMSL) rise across most of Australia's coastline (Al-Nasrawi et al, 2018;Church et al, 2016;McInnes et al, 2015;Zhang et al, 2017). Reefs are sensitive to various parameters such as water depth, light intensity, ocean temperature, ocean chemistry and extreme weather events including storm-surges (Hoegh-Guldberg et al, 2017;Morrison & Hughes, 2016).…”
mentioning
confidence: 95%